Strategies for closing the representation gap in micro and small enterprises - Melisa Serrano; Edlira Xhafa; Edward Webster; Christine Bischoff (International Labour Organization (ILO), 2010)
This working paper is a combination of two reports. The first section is a report by Serrano and Xhafa and it complements the study on the second phase of the Closing the representation gap (Webster et al, 2008). The purpose of this report is to identify critical factors and variables that may affect or influence collective representation of MSE workers. Thus the findings pertaining to non-unionised respondents are highlighted. The report attempts to address the question: What organizing themes and strategies would encourage MSE workers to organize? The report highlights some critical representation factors that could serve as entry points or spaces for collective representation and for enhancing MSE workers willingness to organize and/or join a union. The last section of this working paper is a report on the results of the third and final phase of the Closing the representation gap amongst MSE workers by Webster and Bischoff. The aim of this study was to find ways of strengthening trade union organization amongst workers in micro and small enterprises (MSEs) through conducting a mapping exercise (horizontal and vertical mapping) in nine countries. The report draws on the work of Regalia and identifies two dimensions to union responses to non-standard workers. The first dimension is determined by the degree of awareness of the specific nature of the interests of non-standard workers. The second is the willingness of trade unions to innovate with representation models. The report identifies two crucial conditions for the success of the trade unions which were found in two of the country case studies. Firstly, the mapping process works best where MSE workers are already organized into some form of pre-existing association, either a labour supporting NGO or a worker association that has a firm presence amongst MSE workers. Without this form of embedded solidarity the mapping process fails to find a point of entry and an informal network to engage with. Secondly, both successful country case studies benefited by links with trade union programmes run by university based intellectuals. Secondly the study suggests that new institutional actors are emerging to fill the growing representational gap amongst the traditional industrial relations actors, the state and national trade unions.
Keywords: 330; workers representation; trade union; trade unionization; small enterprise; microenterprise; developed countries; developing countries